Plasma membrane architecture protects Candida albicans from killing by copper - Douglas, Lois M. (PLoS Genet, 2019)
The ability to resist copper toxicity is important for microbial pathogens to survive attack by innate immune cells. A sur7Δ mutant of the fungal pathogen Candida albicans exhibits decreased virulence that correlates with increased sensitivity to copper, as well as defects in other stress responses and morphogenesis. Previous studies indicated that copper kills sur7Δ cells by a mechanism distinct from the known resistance pathways involving the Crp1 copper exporter or the Cup1 metallothionein. Since Sur7 resides in punctate plasma membrane domains known as MCC/eisosomes, we examined overexpression of SUR7 and found that it rescued the copper sensitivity of a mutant that fails to form MCC/eisosomes (pil1Δ lsp1Δ), indicating that these domains act to facilitate Sur7 function. Genetic screening identified new copper-sensitive mutants, the strongest of which were similar to sur7Δ in having altered plasma membranes due to defects in membrane trafficking, cortical actin, and morphogenesis (rvs161Δ, rvs167Δ, and arp2Δ arp3Δ). Consistent with the mutants having altered plasma membrane organization, they were all more readily permeabilized by copper, which is known to bind phosphatidylserine and phosphatidylethanolamine and cause membrane damage. Although these phospholipids are normally localized to the intracellular leaflet of the plasma membrane, their exposure on the surface of the copper-sensitive mutants was indicated by increased susceptibility to membrane damaging agents that bind to these phospholipids. Increased copper sensitivity was also detected for a drs2Δ mutant, which lacks a phospholipid flippase that is involved in maintaining phospholipid asymmetry. Copper binds phosphatidylserine with very high affinity, and deleting CHO1 to prevent phosphatidylserine synthesis rescued the copper sensitivity of sur7Δ cells, confirming a major role for phosphatidylserine in copper sensitivity. These results highlight how proper plasma membrane architecture protects fungal pathogens from copper and attack by the immune system, thereby opening up new avenues for therapeutic intervention.